2007
DOI: 10.3171/foc.2007.22.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Estimated incidence of normal-pressure hydrocephalus and shunt outcome in patients residing in assisted-living and extended-care facilities

Abstract: Object The primary objective of this study was to estimate the prevalence of idiopathic normal-pressure hydrocephalus (NPH), both diagnosed and undiagnosed, among residents of assisted-living and extended-care facilities, by using a practical screening tool. A secondary objective was to evaluate prospectively the diagnosis and outcome of surgical treatment in a subset of patients residing in healthcare facilities who were at risk for idiopathic NPH. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 27 publications
(27 reference statements)
3
45
0
4
Order By: Relevance
“…A special chronic type of communicating hydrocephalus is a normal-pressure hydrocephalus described as a syndrome of ventricular enlargement which occurs in the absence of elevated CSF pressure and is accompanied with gait disturbance, dementia and incontinence (Bergsneider et al, 2005;Hakim and Adams, 1965;Marmarou et al, 2007;Vanneste et al, 1993). Despite the clinical problems indicated in the guidelines for diagnosing and treating such patients, the main interest of this article is to discuss the nature of its development.…”
Section: Communicating Hydrocephalusmentioning
confidence: 99%
“…A special chronic type of communicating hydrocephalus is a normal-pressure hydrocephalus described as a syndrome of ventricular enlargement which occurs in the absence of elevated CSF pressure and is accompanied with gait disturbance, dementia and incontinence (Bergsneider et al, 2005;Hakim and Adams, 1965;Marmarou et al, 2007;Vanneste et al, 1993). Despite the clinical problems indicated in the guidelines for diagnosing and treating such patients, the main interest of this article is to discuss the nature of its development.…”
Section: Communicating Hydrocephalusmentioning
confidence: 99%
“…3 Currently, the estimated number of undetected cases of iNPH may be higher than expected. Approximately 9%-14% of nursing home inhabitants show symptoms of iNPH, 19 and a further increase in cases can be expected given the aging demographic of the population. The economic cost of a comparable dementia disease, such as Alzheimer's disease, is around €43,765 per patient per year.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…23 However, given the significant number of patients who do not show improvement postoperatively, efforts have been taken to better identify potential responders to treatment and potential prognostic predictors that may be controlled. 10 The duration of symptoms prior to surgical treatment is suggested to be a potential predictor of outcomes, with delayed treatment potentially decreasing treatment response. A retrospective study of 132 patients found duration of symptoms and gait as the primary symptom as the only independent predictors of outcomes in the surgical treatment of iNPH.…”
mentioning
confidence: 99%
“…Therefore, the extent and ways in which delayed treatment influences postoperative clinical outcomes remain to be elucidated. Given a prevalence of as much as 1.4% in the elderly adult population, 12,21 and 9%-14% in the assisted-living population, 10,12 it is important to determine to what degree more aggressive identification of iNPH cases for early intervention may prevent morbidity and mortality. The objective of this study was to provide more clarity to these questions and to determine whether the duration of preoperative symptoms alters postoperative outcomes in patients treated for iNPH.…”
mentioning
confidence: 99%